Information system development subject : Education versus industry / Nor Zalina Ismail ... [et al.] - Ismail, Nor Zalina; Razak, Mohd Rizal; Abd Hilmi, Muhammad Qamarul ‘Ashraf; Amran, Mohamad Izzudin; Mohamad Rusdi, Ahmad Fareez; Ismail, Muhammad Syazwan (Universiti Teknologi MARA Cawangan Pahang, 2019)
Our education curriculum should be tailored to the industry practice. Industry always utilize the open source code to develop their software and many of the project in the industry involve updating or maintaining the existing system. Industry also applies the teamwork in their software development project.Nowadays, they also implement collaboration team which is the team member working virtually in different location. This is contrast with the curriculum for Information System Development(ITS332) that require students to develop new real-world computer software. Sport Venue Booking System is the information system project develop by Semester 4 Diploma in Computer Sciences students for ITS 332 subject. The objective of this research is to compare the software development in industry practice versus academic practice by using Sport Venue Booking System as a case study. This research will also compare the practice in SVBS with other higher academic institution. The methodology used is through empirical study in industry practice and other higher academic institution versus the real experience of the supervisor that supervise the project. This research is important to make sure students can be competent in real working environment. Based on the result, there is some lack of the program comprehension skill and collaboration skill necessary for the students to survive in IT world